Escavação da Mamoa de «Monte Maninho» (Serra da Aboboreira-Baião) - Cruz, Domingos J. da (Trabalhos de Antropologia e Etnologia, 2020)
Herewith, are the results of the excavation effected in 1986 at Barrow «Monte Maninho». It concerns a megalithic monument constructed over a plane area and not too well distinct at surface levei. Its architectonic characteristic is similar to that of most monuments of this type existing at Serra da Aboboreira, i.e.: a small earthen tumulus supperficially protected by a layer of small stones and reinforced on its periphery by larger flagstones placed on a slant position. More or less at the central area, slightly towards south-east, would have been the funerary chamber, where a fragmented support was found in situ. This was sustained on the exterior by a small structure of stones and by a beam on the interior. The monument has been revolved various times which affected, mainly, the implantation of the chamber. However, it was still possible to detect the buried ancient soil on the ground of the tumulus, well visible, especially, on the eastern side of the sounding ditch. The assemblage gathered, although scarce, is of importance: besides fragmented ceramic of medieval type, other pre-historical fragments were exhumed (three of which may belong to the same vase) with Bell Beaker's type decoration, which indicate a local adaptation of decoration styles from an outside influence. We also found an ornamental object (a pendant) made of variscite stone. The occurrence of the same type of assemblage found at Barrow 1 of «Chã do Carvalhal», about 450 metres towards NE, as well as at other monuments on the upper planes of Serra da Aboboreira, highlights the problems involving the Bell Beaker's culture on the North of Portugal. As far as Paleoecology is concerned, various samples were taken of sediments and carbonized elements of vegetation, in order to learn about the region's landscape at the time of the monument's construction. Thus, we are publishing the preliminary results of the paleocarpological studies which indicate (although with some reserve due to the fragmented information available) the existence of a significant herbatious substratum not related to agricultura! practice.